Green one-pot three component synthesis of thiazolidine-2,4-dione based bisspirooxindolo-pyrrolidines with [Bmim]BF4: their in vitro and in silico anti-TB studies - Rukyanaik, V.; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (Molecular Diversity, 2025)
A simple and effective three-component one-pot green methodology was employed for the synthesis of a new thiazolidine-2,4-dione based bisspirooxindolo-pyrrolidine derivatives using [Bmim]BF4 ionic liquid via [3 + 2] cycloaddition reaction. It is an environmentally benign, column chromatography-free, shorter reaction time, good yield and easy product isolation method. The synthesized compounds 10a-x, were thoroughly characterized by using various spectroscopic methods like FT-IR, H-1 NMR, C-13 NMR, Mass spectrometry and finally by single crystal X-ray diffraction method. In vitro anti-tubercular (anti-TB) activity studies were carried out on these synthesized compounds, and they showed good to moderate anti-TB activity against Mycobacterium tuberculosis H37Rv strain. The compound 10a exhibited good anti-TB activity, with an MIC (Minimum Inhibitory Concentration) value of 12.5 mu g/mL, and the compounds 10m, 10o and 10r showed moderate activity with an MIC value of 25.0 mu g/mL. Remaining compounds exhibited poor activity against Mycobacterium tuberculosis. Ethambutol, rifampicin and isoniazid were used as standard drugs. Furthermore, in silico molecular docking experiments on the TB protein (PDB ID: 1DF7) were carried out to understand the binding interactions, and they showed least binding energy values ranging from -8.9 to -7.2 kcal/mol.
Keywords: 4-dione based bisspirooxindolo-pyrrolidines; Anti-TB activity; green synthesis; Molecular docking; Thiazolidine-2; [3+2] cycloaddition reaction; [Bmim]BF4